Excavations of the Settlements Artyuschchenko-2 and Vyshesteblievskaya-11 by the Taman Archaeological Group - Kashaev, Sergey V. (Hyperboreus, 2006)
A survey of the excavations in Artyuschchenko-2 and Vyshesteblievskaya-11 (near Taman).